Edukasi Dan Pelatihan Investasi Pasar Modal Indonesia Terhadap Siswa SMA Negeri 6 Ambon - Tualeka, Oki Nurul Asma; Anansya Theresya Lekatompessy; Alfian Fayus Shafar Ambo; Srihayu Umasangaji; Ronald Darlly Hukubun (Yayasan Literasi Sains Indonesia, 2022)
This program of activities aims to increase knowledge about investment in the capital market. This activity is a way to add insight to investing in the capital market and to overcome the influence of low interest in investing in the capital market. In addition, the purpose of this service activity is to provide education and training on investment in the Capital Market for all Amahusu KKN students, teachers who were also present, and students of SMA Negeri 6 Ambon. The activity has provided inclusive account opening in order to increase the opening of Securities Accounts for the IDX Investment Gallery FEB Pattimura University in a sustainable manner. This service activity provides clear results with education and training on Capital Market Investment at SMA Negeri 6 Ambon, which is expected to be an input for students to add insight on how to invest in the capital market. It is also hoped that it can be input for the manager of the Pattimura University Investment Gallery in providing the best public services related to capital market education and training to invest in the Indonesian capital market.